Responsibility of Processed Food Business Actors in the Lawata Market Area for Food Products That Are Not Halal Certified - Idris Saputra; Idaman Idaman; Muhammad Nazar; Endah Widiastuti; Fadhilah Eka Fahrani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Halal certification on a product today has become a must. Because people will be more selective and reluctant to consume products that do not have halal certificates will be abandoned. Many products of processed food business actors in the lawata market area include halal labels but do not get halal certificates. Objectives: This study aims to analyze the responsibility of processed food business actors who distribute products in the lawata market area but do not have a halal certificate. Methods: This study uses a normative legal research method, which means that the author conducts a process to find a rule of law, legal principles, and legal doctrines to answer legal problems and produce an argument, as well as new theories or concepts as prescriptions in solving problems. Results: The legal responsibility of processed food business actors in the lawata market area for non-halal certified food products is regulated in Law Number 33 of 2014 concerning Halal Product Assurance (JPH). Halal certification is mandatory, especially for small Micro Enterprises no later than October 17, 2026 so that food products that are not halal certified and not labeled halal can no longer circulate in the community. Business actors who have obtained a halal certificate are required to include a halal label on the product packaging, certain parts of the product and/or certain places on the product. If business actors include halal labels that do not comply with the regulations, they can be subject to administrative sanctions in the form of: verbal reprimands, written warnings or revocation of products from circulation. Conclusion: These findings highlight the need for processed food business actors to meet the halal standards set by the government to ensure consumer trust, especially in carrying out their beliefs.